COLLABORATIVE LEARNING MODEL: IS IT A SUITABLY LEARNING MODEL TO BE SET-OFF BY INDONESIAN ENGLISH TEACHERS IN SOCIETY 5.0 ERA? - Pohan, Albert Efendi; Gharama, Fadhl Mohammed Awadh; Nugroho, Tri; Mahrani, Mahrani (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
A suitably learning model greatly reassurances the learning efficacy, learning endings and students’ competence in dealing with uncertainty changes in the future. This study drives to legitimize strongly that the collaborative learning model is a suitably model which urgently to be set-off to advance students' competence in fronting the society 5.0 era in Indonesia. To achieve the research ambitions, a qualitative method which systematic literature review design was orchestrated. Research data was poised by collecting 20 previous research judgement from the internet approximately the results of collaborative learning model implementation. Data analysis performance consist of data collection, data presentation, data condensation, and drawing conclusions. The analysis fallouts: 1) Collaborative learning is a learning model which has been empirically proven to be appropriate for Indonesian English teachers to apply in society 5.0 era. 2) The application of collaborative learning model has been empirically proven to be able to increase the competencies needed in society 5.0 era, namely English communication skills, critical thinking, collaborating, and solving problems skills. Afterwards, collaborative learning model must be become skilled theoretically and practically by Indonesian English teachers to produce the excellence graduates to fronting the vagueness in society 5.0 era